KUALITAS SUMBERDAYA MANUSIA PESISIR PANTAI (Studi di Desa Kahakitang Kecamatan Tatoareng Kabupaten Sangihe) - MANUHO, IRMA MULIATI; Ogotan, Martha; Kolondam, Helly (Sam Ratulangi University, 2017)
Summary: Human resources is divided into two, namely, human resource macro is a resident of a countrythat has already entered the age of the work force, either not working or who are already working. Whileunderstanding the micro is the individual work and became a member of a company or institution and iscommonly referred to as employees, workers, employees, workers, labor and others Nawawi (2003:37).Coastal communities need real activities that can build their economies without eliminating the culture andcharacteristics of coastal communities, the required form of community-based activities.This research uses descriptive qualitative approach method. This study describes the data obtainedfrom the results of research on the quality of human resources the coast (study in the village of Kahakitangsub-district of Tatoareng Regency Sangihe). In qualitative research, data collection is done by observation,in-depth interviews and documentation.Based on research results drawn the conclusion that the quality of human resources viewed fromthree indicators categorized quite well. The quality of human resources in particular physical health fishingcommunities quite well seen from the community who care about their own health and are already providinghealth support facilities and infrastructure for the community. For the quality of intellectual (education andtraining) itself is also quite good because there's been an effort of the Government in the fulfillment of theeducational infrastructure and facilities for the community as well as the already existing cooperation withthe Fisheries Agency in empowering human resources especially fishing communities. The quality ofhuman resources in terms of the spiritual quality of its own quite well seen from the daily life of fishingcommunities in the society and harmony between religious communities in compliance, and comply withthe rules made by the Government, as well as the morale of the fishing communities in doing his job. So theGovernment in directing the village empowerment on fishing communities the quality should be on theincrease, the application of the improved quality of HUMAN RESOURCES through three indicators,namely physical quality and health, the quality of intellectual (education and training) and spiritualqualities.This issue became important note for the Government because of the presence of obstacles wherethe quality of HUMAN RESOURCES more precisely to improve the quality of HUMAN RESOURCES wasgoing to be difficult, therefore, needs to be awareness of the Government and the community. The qualityof human resources in realizing better or boost community empowerment which is better then theGovernment should be in driving, giving information, and facilitate Community fishermen.Key Words: Human Resources Quality Coastal Communities